Peningkatan Usaha Bolu Bakery Kreasi Delis Melalui Penambahan Fasilitas Produksi, Packaging Produk, Dan Pelatihan Pembukuan Sederhana Di Kelurahan Sitirejo Iii Kecamatan Medan Amplas Kota Medan Propinsi Sumatera Utara - Dina Arfianti Siregar; Susilawati Susilawati; Siti Asnida Nofianna; Rihat Sebayang (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This bakery sponge business started in 2020 during Covid 19 This business stems from Mrs Desi's ability / talent in making various kinds of sponge ranging from pandan sponge, brownies, cupcakes, black sticky rice sponge, original sponge as well as to help the family economy. This business began to be known by the surrounding community from mouth to mouth promotion because consumers were satisfied with the taste of the sponge cake and also the affordable selling price. Currently, sponge cake production is based on orders. The aim of PKM is to empower MSMEs in the Aneka sponge business sector with production problems, packaging, determining and calculating selling prices and preparing financial reports. The method used is a survey to partners with interviews. The results of PKM activities are that partners get additional production equipment in the form of mxer and standing ovens. Partners get an understanding of good packaging for health, training in determining product selling prices, training in preparing simple financial reports.